2010
DOI: 10.1108/09578231011079575
|View full text |Cite
|
Sign up to set email alerts
|

Modeling cultural context for aspiring women educational leaders

Abstract: Purpose -The purpose of the paper is to discuss and examine the development of frameworks and models to guide future research into studies of women's paths to educational leadership worldwide. Design/methodology/approach -A grounded theory approach to the development of a model of the factors and their interaction that determine the path to educational leadership for women is adopted, drawing on existing research for world-wide studies. Findings -Past studies in this field have focused on identifying barriers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 20 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…Hence rapid reconstruction and modernization movements in society seem to have been much influenced by opportunities for women and might overcome the barriers and enhance the number of studies of women leadership practices in educational settings across the world (Sperandio, 2010). Besides, women principals have expressed as supportive leaders because they were able to solve the problems of their employees.…”
Section: Women As Educational Leadersmentioning
confidence: 99%
“…Hence rapid reconstruction and modernization movements in society seem to have been much influenced by opportunities for women and might overcome the barriers and enhance the number of studies of women leadership practices in educational settings across the world (Sperandio, 2010). Besides, women principals have expressed as supportive leaders because they were able to solve the problems of their employees.…”
Section: Women As Educational Leadersmentioning
confidence: 99%
“…Thankfully, the actual performance of family responsibilities can be rather flexible in this Chinese society, as it is not unusual for women to share their caring duties with kin or contract them out to non-family members. Echoing the findings from some Asian countries (Luke 1998;Sperandio 2010), our women principals were also able to relieve their family duties by soliciting support and help from female family members and even waged household labour. Hannah Obviously, this extra help explains how these Hong Kong women principals were able to juggle their teaching career and family duties.…”
Section: Family Support and Responsibilitiesmentioning
confidence: 82%
“…For instance, in developed countries such as England, Norway and Sweden (Coleman 2007;Davis and Johansson 2005;Moller 2005), the rise is partly the result of equal-opportunity legislation and family-friendly policies. In developing countries, the growth can be attributed to the provision of schooling for girls and the active recruitment of female teachers in response to international calls for the promotion of gender equity (Sperandio 2010).…”
Section: Background and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the complexity of leadership development and professional growth, it is common for neophytes to seek the assistance of more than one person depending on the diverse nature of needs. Furthermore, research has shown that the mentorship of members from underrepresented cultural, linguistic, racial, and gender groups who seek to work within majority communities may require unique sensitivities (see also Kring, 1992; Young and Brooks, 2008; Malone et al , 2010; Sperandio, 2010; McNae, 2010). While formal mentorship and coaching may be helpful, members of these groups may need to seek supports beyond traditional approaches that both affirm and offer tools for mediating difference(s).…”
Section: Exploring Current Practices Of International Leadership Preparationmentioning
confidence: 99%